Burden of gastric cancer in Ecuador (2010–2021): a gender- and age-specific analysis using disability-adjusted life years (DALYs) - Yajamín-Villamarín, Ricardo (Frontiers in Epidemiology, 2025)
BackgroundGastric cancer (GC) is a major public health issue and a leading cause of cancer-related mortality in Ecuador. Despite national cancer control efforts, the burden remains high, with variations by gender and age. This study aimed to quantify the burden of GC in Ecuador from 2010 to 2021 using Disability-Adjusted Life Years (DALYs), providing insights for public health strategies.MethodsA cross-sectional study was conducted using hospital discharge and mortality data from the National Institute of Statistics and Census (INEC). The study included all Ecuadorian individuals diagnosed with GC (ICD-10: C16) from 2010 to 2021. The burden of disease was estimated using DALYs, which combined Years of Life Lost (YLL) and Years Lived with Disability (YLD). Data were stratified by gender and age groups. Analyses were performed using Microsoft Excel and the DALY calculator in R v4.2.1.ResultsBetween 2010 and 2021, GC accounted for 802,135 DALYs in Ecuador, with an annual average of 66,845 DALYs. Males accounted for 57.2% of the total burden. The highest impact was observed in individuals aged 65–69 years. A progressive increase in disease burden was identified, particularly among older age groups.ConclusionsThe findings highlight the need for targeted interventions, including early detection programs, risk reduction strategies, and improved healthcare access. Strengthening public health policies is crucial to mitigating the rising burden of GC in Ecuador.